Negative Response of Lymphocyte Transformation Test (LTT) in a Patient Diagnosed as Stevens-Johnson Syndrome: A Case Report - Ryski Meilia Novarina; Trisniartami Setyaningrum (Faculty of Medicine, Universitas Airlangga, 2015)
Background: Evidences for the key role of T-lymphocytes in the pathophysiology of Stevens-Johnson syndrome (SJS) may be evaluated by drug patch test (DPT) and lymphocyte transformation test (LTT). Purpose: This LTT technology may reveal the role and function of T-lymphocytes for both diagnostic and research purposes. Case: A 33 year-old woman was admited in Dermatology and Venereology Ward at Dr. Soetomo General Hospital with skin and mucous membrane lesions after taking oral medication. Clinical and laboratory examination were performed, establishing the diagnosis of SJS caused by suspect amoxycillin and paracetamol. Case management: The suspected drug was discontinued immediately. Patient was given appropriate supportive treatment, systemic antibiotic, and intravenous dexamethasone with initial adjusted dose of 0.1-0.2 mg/kg/day daily according to clinical improvement. The DPT and LTT were performed 6 months after the lesions healed completely. Both DPT and LTT revealed negative results. LTT is based on the principle that T-cells proliferate in the presence of a specific-antigen, with sensitivity and specificity of 60-70% and 85%, respectively. The LTT revealed negative response, stimulation index (SI<2). Patients with SJS often show weak positive or even negative LTT response. Conclusions: Negative result of DPT in SJS does not exclude suspected drug. LTT is more objective and specific than DPT, however the clinical severity is not associated with high SI values.